Pengaruh Literasi Keuangan, Financial Technology, dan Pengendalian Diri Terhadap Perilaku Keuangan Mahasiswa Jurusan Akuntansi Universitas Negeri Gorontalo - Khairunnisa Alya Putri Ibrahim; Tri Handayani Amaliah; Siti Pratiwi Husain (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of financial literacy, financial technology, and self-control on the financial behavior of students majoring in accounting at Gorontalo State University, both partially and simultaneously. This research uses quantitative research methods. The data source used in this research is primary data obtained from a questionnaire distributed to the population in this research, namely all students majoring in accounting at Gorontalo State University. The results of the research show that partially financial literacy and self-control have a positive and significant effect on the financial behavior of students majoring in accounting at Gorontalo State University, while financial technology literacy does not have a positive and insignificant effect on the financial behavior of students majoring in accounting at Gorontalo State University. Then simultaneously financial literacy, financial technology and self-control have a positive and significant effect on the financial behavior of students majoring in accounting at Gorontalo State University. with a determinant value of 34.8% while the remaining 65.2% is explained by other variables not examined in this study.